Spring Boot with React and AWS : learn to deploy a full stack Spring Boot React application to AWS - Soni, Ravi Kant; Soni, Namrata (Apress, 2021)
Create and deploy full-stack Spring Boot applications with React and AWS. This practical and authoritative guide teaches you the fundamentals of Amazon Web Services with no prior experience. You will start by learning the fundamentals of AWS, including EC2, S3, IAM, and load balancer. Next, you will learn to deploy a Spring Boot REST API to AWS with Elastic Beanstalk, which will give you the ability to build and deploy a Spring Boot application. You will explore the RDS relational database and create an instance of a MySQL database in AWS with RDS. You will then deploy a Spring Boot application to MySQL in AWS and deploy a full-stack Spring Boot React application to AWS using Elastic Beanstalk and S3. Lastly, you will be introduced to ELB, CloudWatch, and Route 53. By the end of this book you will understand full-stack Spring Boot React applications and their deployment. If you prefer "learning by coding" then Spring Boot with React and AWS is the book for you. You will: Review the fundamentals of Amazon Web Services Install a Spring Boot REST API with CRUD operation to AWS using AWS Elastic Beanstalk Deploy a full-stack Spring Boot React application to AWS using AWS Elastic Beanstalk and S3 Work with MySQL as a database in AWS using RDS Use Spring Boot with React and AWS